Pengaruh model interactive-case based learning terhadap kemampuan berpikir kritis peserta didik kelas v pada pembelajaran ipa sekolah dasar - Alia Rahmah Fathori; Roy Ardiansyah (Universitas Sebelas Maret, 2025)
Critical thinking skills are one of the important competencies that need to be developed in the learning process, especially in facing the challenges of the 21st century. The Interactive-Case Based Learning (ICBL) learning model is present as an innovative approach that can increase students' active involvement in the learning process. Through real case-based problem solving and interactive discussion activities, students are trained to analyze information, evaluate various alternative solutions, and draw logical and rational conclusions. This active involvement is an important factor in developing critical thinking skills. This study uses a quantitative approach with an experimental method to test the effect of the ICBL model on students' critical thinking skills. The design used is a pretest-posttest control group design, by comparing learning outcomes between the experimental group using the ICBL model and the control group using the conventional model. The results of the study showed that the ICBL model had a positive and significant effect on improving students' critical thinking skills. Thus, this model can be used as an effective learning alternative in developing students' critical thinking skills